Tuning the anticancer properties of Pt(ii) complexes via structurally flexible N-(2-picolyl)salicylimine ligands. Issue 42 (27th September 2022) - Al-Rashdi, Kamelah S.; Babgi, Bandar A.; Ali, Ehab M. M.; Davaasuren, Bambar; Jedidi, Abdesslem; Emwas, Abdul-Hamid M.; Alrayyani, Maymounah A.; Jaremko, Mariusz; Humphrey, Mark G.; Hussien, Mostafa A.
Abstract : Three tridentate Schiff base ligands were synthesized from the reactions between 2-picolylamine and salicylaldehyde derivatives (3-ethoxy (OEt), 4-diethylamino (NEt2 ) and 4-hydroxy (OH)). Abstract : Three tridentate Schiff base ligands were synthesized from the reactions between 2-picolylamine and salicylaldehyde derivatives (3-ethoxy (OEt), 4-diethylamino (NEt2 ) and 4-hydroxy (OH)). Complexes with the general formula Pt(N^N^O)Cl were obtained from reactions between the ligands and K2 PtCl4 . The ligands and their complexes were characterized by NMR spectroscopy, mass spectrometry and elemental analysis. Further confirmation of the structure of Pt-OEt was achieved by single-crystal X-ray diffraction. The DMSO/chlorido exchange process at Pt-OEt was investigated by monitoring the change in conductivity, revealing very slow dissociation in DMSO. Moreover, solvent/chlorido exchange for Pt-OEt and Pt-NEt2 were investigated by NMR spectroscopy in DMSO and DMSO/D2 O; Pt-NEt2 forms an adduct with DMSO while Pt-OEt forms adducts with DMSO and water. The DNA-binding behaviour of the platinum(ii ) complexes was investigated by two techniques. Pt-NEt2 has the best apparent binding constant. The intercalation mode of interaction with ct-DNA was suggested by molecular docking studies and the increase in the relative viscosity of ct-DNA with increasing concentrations of the platinum(ii ) complexes. However, the gradual decrease in the relative viscosity over time at constant concentration of platinum(ii ) complexes indicated a shift from intercalation to a covalent binding mode. Anticancer activities of the ligands and their platinum(ii ) complexes were examined against two cell lines. The platinum(ii ) complexes exhibit superior cytotoxicity to that of their ligands. Among the platinum(ii ) complexes, Pt-OEt possesses the best IC50 against both cell lines, its cytotoxicity being comparable to that observed for cisplatin. Cell cycle arrest in the HepG2 cell line upon treatment with Pt-OEt and Pt-NEt2 was investigated and compared to that of cisplatin; the change in the cell accumulation patterns supports the presumption of an apoptotic cell death pathway. The optimized structures of the B-DNA trimer adducts with the platinum complexes showed hydrogen-bonding interactions between the ligands and nucleobases, affecting the inter-strand hydrogen bonding within the DNA, and highlighting the strong ability of the complexes to induce conformational changes in the DNA, leading to the activation of apoptotic cell death. In summary, the current study demonstrates promising new anticancer platinum(ii ) complexes with highly flexible tridentate ligands; the functional groups on the ligands are important in tuning their DNA binding/anticancer properties.